What drives the success and failure of climate change adaptation projects? A qualitative comparative analysis - Pacillo, Grazia; Nguyen, Nam; Paustyan, Ekaterina; Cavatassi, Romina; Astralaga, Margarita; Laderach, Peter (Springer, 2024)
The ongoing climate crisis is significantly impacting the livelihoods of millions of farmers worldwide. Despite various efforts, many climate adaptation projects have struggled to yield the desired results. What determines the success or failure of these projects? Utilizing Qualitative Comparative Analysis, we delve into the intricate connections among climate patterns, resilience, and adaptation initiatives. Through a case study of the International Fund for Agricultural Development (IFAD) program, we aim to discern critical factors contributing to success or failure. Our findings underscore the importance of integrating climate trends into adaptation strategies, which fosters a deeper comprehension of climate-related risks and bolsters the resilience of smallholder farmers. Notably, no single factor can solely account for success; rather, it is the combined presence or synergy of multiple factors that drive effective adaptation interventions. Key elements include adept project management, improved institutional coordination, scalability of interventions, bolstering beneficiaries' coping mechanisms, and fostering innovation. It is the harmonious interplay of these components that paves the way for successful outcomes.